2015
DOI: 10.1186/s13019-015-0302-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and surgical treatment for isolated tricuspid libman-sacks endocarditis: a rare case report and literatures review

Abstract: Libman-Sacks endocarditis (LSE), characterized by verrucous vegetations formation, is a typical cardiac manifestation of autoimmune diseases such as systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). It primarily leads to lesions of cardiac valves and mostly involved valves are mitral and aortic, but isolated tricuspid valve involvement is exceptional. Here we reported a 20-years-old female with past SLE history suffered from acute right heart failure caused by multiple tricuspid vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Association between APS and NBTE presenting as a myxoma-like mass has been previously described in the literature, but only in female patients [ 4 ]. The same has been the case for isolated tricuspid valve NBTE associated with APS [ 8 ]. A literature review revealed only scarce reported cases of NBTE presenting as large vegetations in male patients with APS, and those found were restricted to the aortic valve, which is a more common site of NBTE involvement [ 10 ].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Association between APS and NBTE presenting as a myxoma-like mass has been previously described in the literature, but only in female patients [ 4 ]. The same has been the case for isolated tricuspid valve NBTE associated with APS [ 8 ]. A literature review revealed only scarce reported cases of NBTE presenting as large vegetations in male patients with APS, and those found were restricted to the aortic valve, which is a more common site of NBTE involvement [ 10 ].…”
Section: Discussionmentioning
confidence: 54%
“…Nonbacterial thrombotic endocarditis is usually characterized by sessile, wart-like vegetations that range from pinhead to 3-4 mm in size and most commonly involve the mitral and aortic valves [ 3 ]. Although rare, several cases of isolated tricuspid valve involvement related to APS have been reported in the literature [ 8 ]. Cardiac masses in patients with APS have proved challenging to physicians, with NBTE vegetations being occasionally misdiagnosed as myxomas due to presenting with similar characteristics on imaging, as well as the possibility of APS and a primary cardiac neoplasm coexisting [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The landmark lesion of IE is the vegetation (Figure 1) [57]. In this context, IDUs population with vegetations >20 mm may present higher embolic risk [58] and higher mortality as well [25,58,59].…”
Section: Diagnosismentioning
confidence: 99%
“…TOE has higher sensibility in the detection of pulmonary vegetations [62]. When clinical manifestations sustain IE with negative or unclear TTE, TOE has high sensitivity (>90%) and may reveal: (1) vegetations; (2) paravalvular or intracardiac abscess, (3) new valvular regurgitations, and (4) prosthetic valve dehiscence (Figure 2) [57,63,64].…”
Section: Diagnosismentioning
confidence: 99%